Safety assessment of propyl-propane-thiosulfonate (PTSO): 90-days oral subchronic toxicity study in rats. (October 2020) - Lira, Antonio Cascajosa; Prieto, Ana Isabel; Baños, Alberto; Guillamón, Enrique; Moyano, Rosario; Jos, Angeles; Cameán, Ana M.
Abstract: Propyl-propane-thiosulfonate (PTSO) is one of the main organosulfur compounds present in Allium essentials oil. Different applications in the food sector have been proposed for PTSO, such as food and feed additive and as active packaging. However, the authorization of its use depends on its toxicity profile. Thus, as a part of its safety assessment, in this work a repeated dose 90-day oral toxicity study has been conducted for the first time in rats following the OECD guideline 408. PTSO was administered to groups of 10 male and 10 female rats at dose levels of 0, 14, 28, and 55 mg/kg/day. No clinical signs or mortality and no changes in body weight, food consumption and feed conversion efficiency were detected through the study. Moreover, no treatment-related changes in hematological and biochemical parameters were observed, for either sex or dose groups. The histopathology study performed revealed no differences in organ weights, and no morphological and histopathological changes were observed. Based on these results, the no-observed-adverse-effect level (NOAEL) of PTSO was judged to be ≥ 55 mg/kg/day for both sexes. Highlights: A 90 days oral toxicity study was conducted with propyl-propane-thiosulfonate. PTSO did not induce toxic effects at the highest dose assayed (55 mg/kg/day). NOAEL for PTSO was estimated to be ≥ 55 mg/kg/day.